Effectiveness of a Proposed Educational Program Based on Specific Exercises to Develop Motor Abilities and Technical Proficiency in Shot Put Competition Among Physical Education Students - Rana Mohammed Mutair (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
This study aimed to develop a proposed training program based on specific exercises to enhance motor skills agility, coordination, and balance. And to determine its impact on technical performance and distance achieved in shot put. The researcher applied two equivalent groups in an experimental design, using a sample of 30 students from Wasit University. Program comprised eight training sessions, delivered twice weekly for four weeks. Results demonstrated superiority of experimental group in all post-tests, indicating that specific exercises effectively addressed technical errors during gliding phase and improved movement flow. Conclusion proposed educational program achieved a qualitative leap in motor skills and technical efficiency for  weightlifting activity, and proved that  variety in exercises creates a spirit of excitement and suspense and stimulates learning. Students' motor skills, technical performance, and weightlifting accomplishment were all enhanced by selecting workouts in accordance with the rule of learning (from easy to tough). The study suggests incorporating certain motor workouts into throwing event curriculum.